A rare cause of acute abdomen: Ovarian torsion due to dermoid cyst: Ovarian torsion due to dermoid cyst - Akça, Hatice Şeyma; Atik, Dilek; Köse , Fulya (Journal of Surgery and Medicine, 2023)
Dermoid cysts are one of the most common causes of ovarian torsion. The causes of acute abdominal pain are mostly caused by the diagnosis of acute appendicitis, acute pancreatitis, and mesenteric ischemia, and the incidence of ovarian torsion is not known exactly. Although ovarian torsion is very rare, it ranks first among the indications for gynecological emergency surgery. A rare case of a non-ruptured dermoid cyst causing ovarian torsion in the emergency room is presented.